EVALUATION OF NIGERIAN CASHLESS PAYMENT POLICY AND ITS IMPACT ON ECONOMIC GROWTH: A SYNTHETIC REVIEW - Peter Anuforo; Mathias Joel; Bitrus Kolo Ndirmbitah; Felicia Maindo (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aimed to provide a comprehensive analysis of the existing literature on the impact of cashless payment policy on economic growth in Nigeria. The paper is designed to provide a first broad overview for academic researchers and provide a practical financial policy for determining the impact of cashless payment policy on economy growth. This study conducted a critical literature review (survey) on the relation between cashless payment policy and economic growth. This research was explorative, descriptive and was based on documentary review. The study applied qualitative text data analysis approach and examined documents and systematically interprets the information so as to allow the researcher to draw inference about the issues of interest. Thus, the identified articles were screened using the content-centric analysis technique so as to align with the objective of the study by searching for suitable keywords in line with the theme of the study. Hence, the study was carried out systematically through an article search engine using the keywords